Recent developments in mobile-assisted vocabulary learning: a mini review of published studies focusing on digital flashcards - Teymouri, Reza (Frontiers in Education, 2024)
This mini review provides a concise overview of recent developments in mobile-assisted vocabulary learning (MAVL) and compares its effectiveness to traditional methods in English as a Foreign Language (EFL) settings. The review synthesizes findings from recent empirical studies, highlighting how MAVL, particularly digital flashcards, promotes learner autonomy, engagement, and long-term vocabulary retention through features like spaced repetition and gamification. Traditional methods such as paper flashcards, while effective in structured classroom settings, lack the interactive and personalized benefits of MAVL. The review also discusses existing research gaps, including the need for further investigation into productive vocabulary use and long-term retention. Future developments in the field may include hybrid approaches that combine the strengths of both traditional and digital methods. This review aims to provide language teachers and researchers with an up-to-date understanding of MAVL and its potential to enhance EFL vocabulary acquisition.